2019
DOI: 10.1213/ane.0000000000003553
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Versus Protocolized Fluid Management Using Noninvasive Hemodynamic Monitoring (Clearsight System) in Patients Undergoing Moderate-Risk Abdominal Surgery

Abstract: Advances in noninvasive hemodynamic monitoring systems allow delivery of goal-directed fluid therapy and could therefore be used in less-invasive surgical procedures. In this randomized controlled trial, we compared closed-loop-assisted goal-directed fluid therapy using a noninvasive cardiac output (Clearsight system) monitor (personalized approach) to a protocolized fluid therapy approach in 40 patients undergoing moderate-risk laparoscopic abdominal surgery. Cardiac output and stroke volume variations were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 15 publications
0
40
1
3
Order By: Relevance
“…The total sample size was <100 participants for 33 studies (Bahlmann et al, 2019;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Cecconi et al, 2011;Colantonio et al, 2015;El Sharkawy et al, 2013;Funk et al, 2015;Han et al, 2016;Jammer et al, 2015;Joosten et al, 2019;Kaufmann et al, 2018;Kim et al, 2018;Kumar et al, 2016;Lobo et al, 2000;Mayer et al, 2010;Mikor et al, 2015;Mythen & Webb, 1995;Peng et al, 2014;Reisinger et al, 2017;Scheeren et al, 2013;Senagore et al, 2009;Shoemaker et al, 1988;Sinclair et al, 1997;Ueno et al, 1998;Van der Linden et al, 2010;Venn et al, 2002;Weinberg et al, 2017;Weinberg et al, 2019;Wu et al, 2017;Yin et al, 2018;Zakhaleva et al, 2013;Zeng et al, 2014;Zhang et al, 2013) (50%) and the majority (77%) were conducted in a single centre setting (Bartha et al, 2013;Bender et al, 1997;Benes et al, 2010;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Boyd et al, 1993;Cecconi et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
“…The total sample size was <100 participants for 33 studies (Bahlmann et al, 2019;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Cecconi et al, 2011;Colantonio et al, 2015;El Sharkawy et al, 2013;Funk et al, 2015;Han et al, 2016;Jammer et al, 2015;Joosten et al, 2019;Kaufmann et al, 2018;Kim et al, 2018;Kumar et al, 2016;Lobo et al, 2000;Mayer et al, 2010;Mikor et al, 2015;Mythen & Webb, 1995;Peng et al, 2014;Reisinger et al, 2017;Scheeren et al, 2013;Senagore et al, 2009;Shoemaker et al, 1988;Sinclair et al, 1997;Ueno et al, 1998;Van der Linden et al, 2010;Venn et al, 2002;Weinberg et al, 2017;Weinberg et al, 2019;Wu et al, 2017;Yin et al, 2018;Zakhaleva et al, 2013;Zeng et al, 2014;Zhang et al, 2013) (50%) and the majority (77%) were conducted in a single centre setting (Bartha et al, 2013;Bender et al, 1997;Benes et al, 2010;Bisgaard et al, 2013a;Bisgaard et al, 2013b;Boyd et al, 1993;Cecconi et al, 2011;…”
Section: Resultsmentioning
confidence: 99%
“…Partial CO 2 rebreathing Partial CO 2 rebreathing is a non-invasive technique that estimates CO by using respiratory gas analysis and pulse oximetry. Many studies suggest moderate to good agreement with CO measurements obtained by the thermodilution method during surgery and in ICU mechanically ventilated patients [84][85][86][87], but there was a great bias during a period of rapidly changing shunt and dead space, as occurs at the start of one-lung ventilation [88]. Although many studies have shown that CO was underestimated by the partial CO 2 rebreathing method compared with the thermodilution method, it still can be used to guide haemodynamic management during surgery [87,89].…”
Section: Volume Clamp and Radial Artery Applanation Tonometrymentioning
confidence: 99%
“…There are no guidelines concerning perioperative fluid therapy for patients with end-stage renal failure (ESRF) [1]. Nearly all the studies of perioperative fluid therapy excluded patients with ESRF because of their physical condition [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%